Combined single- and dual-energy CT workflow for dose calculation in radiotherapy - Hella Sand; Jens Edmund; Ane Appelt; Patrick Wohlfahrt; Vicki Trier Taasti; Laurids Østergaard Poulsen; Jimmi Søndergaard; Martin Skovmos Nielsen (Acta Oncologica)
Background and purpose: Dual-energy computed tomography (DECT) is increasingly used in radiotherapy delineation due to its enhanced soft tissue contrast. DECT also supports direct dose calculation. However, as most current DECT scanners allow for use in only certain body regions, conventional single-energy computed tomography (SECT) is still needed for some patients. A safe clinical introduction of DECT thus requires a combined workflow. This study therefore investigates whether a unified Hounsfield look-up table (HLUT) can be applied across SECT and DECT reconstructions.